2001
DOI: 10.1007/s00455-001-0088-2
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Oral Appliance Therapy: Are Oral Skills and Growth Maintained One Year after Termination of Therapy?

Abstract: To determine the impact of intraoral appliance (ISMAR) therapy on functional feeding skills and growth, children with cerebral palsy and moderate dysphagia were followed a full year after termination of one year of ISMAR therapy. Seventeen children, 6.6-15.4 years old (mean age = 10.2 +/- 3.0 years), were divided into two groups: group A (n = 9) continued to wear the appliance and group B (n = 8) no longer wore the appliance. Generalized estimating equations (GEE) were used to test differences between the two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 14 publications
0
32
0
Order By: Relevance
“…Sixteen studies investigated the effects of OME on swallowing in children 14,25–39 . Eight studies examined the effects of OME on swallowing physiology (), six studies examined functional swallowing outcomes (), and five studies explored the effects of OME on drooling ().…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sixteen studies investigated the effects of OME on swallowing in children 14,25–39 . Eight studies examined the effects of OME on swallowing physiology (), six studies examined functional swallowing outcomes (), and five studies explored the effects of OME on drooling ().…”
Section: Resultsmentioning
confidence: 99%
“…ISMAR) to standard rehabilitation received at school. Gisel et al 31 . evaluated children who continued to wear the ISMAR for a second year compared with those who did not.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have also found that the GVA is not sensitive to small changes in ingestive skills [10]; therefore, we use it strictly as a diagnostic tool to determine the severity of an eating impairment [14]. On the other hand, the FFAm has proven to be an excellent tool to measure change following oral-motor therapies [10,11,26,27].…”
Section: Psychometric Properties Of Testsmentioning
confidence: 97%
“…A number of studies have investigated feeding skills patterns and health outcomes in children with CP (Gisel, Alphonce, & Ramsay, ; Reilly, Skuse, & Plobete, ; Sullivan et al, ; Troughton & Hill, ; Vik, Skrove, Dollner, & Helland, ; Yousafzai et al, ). It has also been shown that with proper interventions on knowledge and caregiver support in the positioning and use of utensils, feeding skills and child–caregiver interactions during feeding can be improved (Adams et al, ; Bailey & Angell, ; Das, Zaman, Hasan, Barua, & Chowdhury, ; Gisel, Applegate‐Ferrante, Benson, & Bosma, ; Gisel, Applegate‐Ferrante, Benson, & Bosma, ; Gisel, Haberfellner, & Schwartz, ; Haberfellner, Schwartz, & Gisel, ; Johnson et al, ; Marchand & Motil, ; Vekerdy, ).…”
Section: Introductionmentioning
confidence: 99%